Nutrient, amino acids, phytochemical and antioxidant activities of common Nigeria indigenous soups - Ayo Oluwadunsin Olugbuyi; Timilehin David Oluwajuyitan; Ibidapo Nathaniel Adebayod; Ugochukwu Miracle Anosike (Journal of Agriculture and Food Research, 2023)
Indigenous vegetables have gained attention due to their dietary fibre, mineral, amino acids, phytochemicals, and antioxidant activities. Bitter leaf (BL); Efinrin leaf (EF); Koro owu or cotton seed leaf (KO); Marugbo leaf (MA); Ewedu leaf (EW) and Ira leaf (IR) are common Nigeria indigenous vegetables. These vegetables were processed into soup and analysed for proximate, mineral, amino acids, phytochemicals, and antioxidant activities. The crude fibre content of the vegetable ranged from 2.70 g/100 g in BL to 8.63 g/100 g in MA. It was observed that MA soup had the highest calcium content (42.89 mg/100 g) while the phytochemicals (mg/g) - tannin, phytate, oxalate, total phenol and total flavonoids values ranged as follows: 0.80–7.30; 2.00–32.76; 0.63–5.77; 1.06–9.12 and 0.61–19.50 respectively. The branch chain amino acid content ranged from 10.75 in MA to 14.67 in BL, total non-essential amino acids (35.32 in BL – 57.97 g/100 g in KO) and total essential amino acid (25.70 in MA – 32.34 g/100 g in KO) respectively. The DPPH ranged between 32.32 and 97.24%. Hence, consumption of these processed Nigerian indigenous vegetables soups may be beneficial in prevention and treatment of diet related diseases.